Mengungkap Kajian Makna dalam Tradisi Pawai Maulid Nabi Muhammad Saw di Kawasan Masjid Kauman, Kecamatan Semarang Tengah, Kota Semarang - Amri, Daffa; Sahari, Dariel Ramadhan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to reveal the symbolic meanings and socio-religious values embedded in the Maulid Prophet Muhammad Saw Parade Tradition in the Kauman Mosque area of Semarang, as well as to analyze its important role in shaping community religious behavior and solidarity. The research also seeks to identify how language and symbols used in the Maulid Parade construct the community’s religious identity and reflect the historical relationship between Javanese, Arab, and Chinese cultures. This study employs a qualitative descriptive approach supported by a theoretical framework grounded in ethnolinguistics. Data were collected through observation, interviews, and documentation, with the primary sources obtained from direct interviews. The data consist of verbal elements (utterances, salawat, linguistic terms) and non-verbal elements (processions, cultural symbols) found throughout the event. Content analysis was used as the data analysis method. The results indicate that the Maulid Parade functions not only as a religious tradition but also as a complex form of cultural communication. From an ethnolinguistic perspective, the parade conveys social and spiritual values through a fusion of language and symbolic expressions. The essence of this tradition lies in expressing love for the Prophet Muhammad Saw and disseminating religious teachings so that he continues to be remembered as the best role model (uswatun hasanah). The KKQ Parade also strengthens social solidarity and serves as a medium for preserving local cultural traditions, illustrating an acculturation of Arab, Javanese, and Chinese cultures similar to the symbolic. Thus, the parade reflects the dynamic socio- religious identity of the Kauman community and its commitment to the values of Islam Nusantara.